Experimental pressure dependence of the accelerated current in the chamber of the sirius synchrotron; Russian Physics Journal; Vol. 12, № 2 - Chuchalin I. P. Ivan Petrovich (1969, 1969)
An experimental study of the dependence of the accelerated charge in the synchrotron on the vacuum-chamber pressure is reported. The results are compared with calculations; in the pressure range 5 · 10-6-2 · 10-5 torr, the experimental and calculated results agree well